Solar photocatalysts based on titanium dioxide nanotubes for hydrogen evolution from aqueous solutions of ethanol. (10th May 2021) - Valeeva, Albina A.; Dorosheva, Irina B.; Kozlova, Ekaterina A.; Sushnikova, Anna A.; Kurenkova, Anna Yu; Saraev, Аndrey А.; Schroettner, Hartrmuth; Rempel, Аndrey А.
Abstract: Titanium foil was anodized to grow titanium dioxide nanotubes (TiO2 NT) by using an original technique. A solution of ethylene glycol and ammonium fluoride with a concentration of 0.5 wt% was employed as electrolyte, corrosion-resistant steel was chosen as the cathode material. Anodic oxidation was carried out potentiostatically at a voltage of 60 V at ambient temperature for 90 min. Modification of as prepared TiO2 NT were modified by calcination in air at 350°C for 4 h. Platinization of TiO2 NT was carried out by chemical reduction of platinum from H2 PtCl6 solution by NaBH4 solution. Photocatalyst characterization was performed by using XRD, BET, SEM, XPS techniques. It was found that the calcination of as-prepared TiO2 NT leads to 6-fold increase of the photocatalytic activity under UV-irradiation. The enhanced activity of TiO2 NT is associated with the developed specific surface area and unique morphology of TiO2 NT. This results in high rate of separation of photogenerated excited electrons and holes. Due to high separation rate the catalytic activity increases substantially. Graphical abstract: Image 1 Highlights: The nanotubular titanium dioxide TiO2 NT were grown using an original technique. The activity of Pt/TiO2 was measured in the reaction of ethanol oxidation in water. The activity of Pt/TiO2 was found to be 6 times higher compared to initial TiO2 NT. High activity owing to high defectiveness, special morphology and developed surface.